Peran Pendidikan Islam dalam Menanggulangi Dekadensi Moral di SMP Muhammadiyah Limbung Gowa - Nurul Haeriyah Ridwan (Matan : Journal of Islam and Muslim Society, 2022)
The moral decadence that appears in some of the younger generation today has a very big effect, because teenagers are a big hope as the nation's successors to become better. The purpose of this research was to find out the description of Moral Decadence in SMP Muhammadiyah Limbung, and to know the role of Islamic Education in tackling Moral Decadence in SMP Muhammadiyah Limbung. This research is a qualitative research,. The research will take place in Gowa district, precisely at Muhammadiyah Limbung Junior High School, Gowa Regency. The resource persons in this study are people who are considered competent and have knowledge, namely the Principal, Educators, and Students, Muhammadiyah Limbung, Gowa Regency. The author will carry out defects and efforts to collect information about the state of a symptom that occurs when the research is carried out systematically through the data analysis steps used in this study are: (1) Data reduction (2) Data display (3) Conclusion drawing. Based on the results of the research and discussion, it was found that (1) Moral decadence that occurred at SMP Muhammadiyah Limbung were: Fighting, Using Drugs (sucking glue and illegal drugs), Watching Porn Videos, Saying bad words, and not attending the prayer together organized by the school. Factors causing moral decadence in Muhammadiyah Limbung Junior High School are the lack of attention and supervision from both parents of students and providing indirect examples, and (2) the role of Islamic education in overcoming Moral Decadence in Limbung Muhammadiyah Junior High School: Educators at Limbung Muhammadiyah Junior High School promote extracurricular activities and Islamic education